A‎ ‎solution ‎procedure ‎to ‎solve‎ multi-objective linear fractional programming problem in neutrosophic fuzzy environment - Elham Hosseinzadeh (Journal of Mahani Mathematical Research, 2023)
In this paper, an attempt has been taken to develop a method to solve the neutrosophic multiobjective linear fractional programming (NMOLFPP) problem. In the first step of our method, the problem is linearized based on some transformations. Then, the linearized model is reduced to a crisp multi-objective programming problem with the help of the accuracy function for each objective. In the following, we extended Zimmerman’s approach to maximize the truth membership and minimize the indeterminacy and falsity membership functions in the solution procedure. Finally, to illustrate the proposed approach, a numerical example is included.